2017
DOI: 10.1007/s00702-017-1774-z
|View full text |Cite
|
Sign up to set email alerts
|

Chronic MPTP administration regimen in monkeys: a model of dopaminergic and non-dopaminergic cell loss in Parkinson’s disease

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative disorder clinically characterized by cardinal motor deficits including bradykinesia, tremor, rigidity and postural instability. Over the past decades, it has become clear that PD symptoms extend far beyond motor signs to include cognitive, autonomic and psychiatric impairments, most likely resulting from cortical and subcortical lesions of non-dopaminergic systems. In addition to nigrostriatal dopaminergic degeneration, pathological examination of PD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 337 publications
(419 reference statements)
3
39
0
Order By: Relevance
“…The severity of the parkinsonian motor signs had to be stable for a period of at least 6 weeks after the last MPTP injection before the monkeys were considered parkinsonian for this study. We have used the same protocol in many previous studies (Bogenpohl, Galvan, Hu, Wichmann, & Smith, 2013;Devergnas et al, 2016;Galvan et al, 2014;Hadipour-Niktarash, Rommelfanger, Masilamoni, Smith, & Wichmann, 2012;Masilamoni et al, 2010;Masilamoni et al, 2011;Masilamoni & Smith, 2018;Mathai et al, 2015;Villalba, Wichmann, & Smith, 2014).…”
Section: Mptp Treatment and Assessment Of Parkinsonismmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of the parkinsonian motor signs had to be stable for a period of at least 6 weeks after the last MPTP injection before the monkeys were considered parkinsonian for this study. We have used the same protocol in many previous studies (Bogenpohl, Galvan, Hu, Wichmann, & Smith, 2013;Devergnas et al, 2016;Galvan et al, 2014;Hadipour-Niktarash, Rommelfanger, Masilamoni, Smith, & Wichmann, 2012;Masilamoni et al, 2010;Masilamoni et al, 2011;Masilamoni & Smith, 2018;Mathai et al, 2015;Villalba, Wichmann, & Smith, 2014).…”
Section: Mptp Treatment and Assessment Of Parkinsonismmentioning
confidence: 99%
“…To verify denervation of the nigro-striatal pathway by MPTP intoxication, sections at the level of the striatum and the substantia nigra from MPTP-treated monkeys were stained with mouse anti-TH antibody (Table 2; RRID:AB_2201528), as described in our previous studies (Bogenpohl et al, 2013;Devergnas et al, 2016;Galvan et al, 2014;Hadipour-Niktarash et al, 2012;Masilamoni et al, 2010;Masilamoni et al, 2011;Masilamoni & Smith, 2018;Mathai et al, 2015).…”
Section: Striatal Tyrosine Hydroxylase (Th) Immunostainingmentioning
confidence: 99%
“…In addition to parkinsonian motor signs, chronically MPTP-treated monkeys display early cognitive dysfunction (Roeltgen and Schneider, 1991;Schneider and Kovelowski, 1990;Schneider et al, 2010;Slovin et al, 1999), alterations in sleep, social relationships, olfaction, and gastrointestinal pathologies (Almirall et al, 1999;Barraud et al, 2009;Chaumette et al, 2009;Durand et al, 2015;Phillips et al, 2017). In line with these complex neurobehavioral alterations, profound loss of central noradrenergic, serotonergic and thalamic neurons, and the development of synuclein aggregates have been described in chronically MPTP-treated monkeys and mice (Fornai et al, 2005;Masilamoni et al, 2011;Masilamoni et al, 2017;Masilamoni and Smith, 2018;Vivacqua et al, 2019). Another monkey study reported as much as 70% reduction in the number of catecholaminergic myenteric neurons (Chaumette et al, 2009); however, the effects of chronic systemic MPTP on in vivo gastrointestinal functions, inflammation, and bacterial composition have not been evaluated in non-human primates.…”
Section: Introductionmentioning
confidence: 96%
“…The MPTP-treated rhesus macaque monkey model is commonly seen as a "gold standard" model that closely mimics the clinical motor symptoms and the nigrostriatal dopaminergic loss of PD, but the neuropathologic and behavioral effects of the drug extend beyond the ventral midbrain dopaminergic cell groups and parkinsonian motor signs when low doses of MPTP are administered chronically to monkeys and mice (Emborg, 2007;Masilamoni et al, 2011;Masilamoni et al, 2017;Masilamoni and Smith, 2018;Vivacqua et al, 2019) Chronic systemic MPTP administration over several weeks to months allows the slow development of parkinsonism that is more similar to PD, importantly creating a window of time to evaluate early premotor symptoms including inflammation and nonmotor manifestations that are alike impaired in PD. Dysregulated cytokines have been described in non-human primates treated with MPTP (Mondal et al, 2012;Roy et al, 2015) or systemically (Barcia et al, 2005;De Pablos et al, 2009), but the trajectory of the inflammatory environment has not been detailed throughout the gradual progression of MPTP-induced neuropathology and related behavioral changes.…”
Section: Introductionmentioning
confidence: 99%
“…Because these neurons are non-existent in rodents, and undergo significant alterations in diseased states, the use of NHPs to understand their role in normal basal ganglia functions and in the pathophysiology of basal ganglia disorders is essential. This manuscript is followed by a series of reviews on the use of the MPTP-treated NHP model of PD to study the pathogenesis, and test new therapies for PD and l-DOPA-induced dyskinesias (Morissette and Di Paolo 2017;Blesa et al 2017;Masilamoni and Smith 2017;Vermilyea and Emborg 2017). In addition, Masilamoni and Smith (2017) highlight the fact that the chronic intoxication of monkeys with MPTP results in an animal model that displays brain pathology that extends far beyond the midbrain dopaminergic cell groups to include other brainstem monoaminergic neurons and intralaminar thalamic cells, suggesting that chronically MPTPtreated monkeys can potentially be used as an animal model to study the pathophysiology and therapeutics of non-motor symptoms of PD.…”
mentioning
confidence: 99%